Encyclopedia of environmetrics - El-Shaarawi, A. H.; Piegorsch, Walter W. (Hoboken, N.J. Wiley, 2012)
An expanded and revised edition of an essential reference work for university libraries, research laboratories, government institutions and consultancies concerned with the environmental sciences -- Provided by publisher.
6 volume set.
Includes bibliographical references and index.
Keywords: Environmental sciences -- Statistical methods -- Encyclopedias; Environmental sciences -- Methodology -- Encyclopedias